Effects of platelet-rich plasma against experimental ischemia/reperfusion injury in rat testis - YARAT, AYŞEN; ŞEKERCİ, ÇAĞRI AKIN; ÇETİNEL, ŞULE; ŞENER, TARIK EMRE; TANIDIR, YILÖREN (ELSEVIER SCI LTD, 2017)
Background Testicular torsion is a common problem and, to date, there is no agent to preserve testicular function following detorsion. Platelet-rich plasma (PRP), with its rich growth factor composition, has proven beneficial in regenerative therapy. It is believed that PRP has not been studied in testis for ischemia/ reperfusion (I/R) injury. Objective This study investigated the effect of PRP in an I/R rat model 1 month after detorsion. Study design Of 24 adult male Spraguee-Dawley rats, 18 were randomly assigned into three groups, with six in each: control, I/R and I/R + PRP. The PRP was prepared from the remaining six. Each group underwent right orchiectomy. Ischemia was performed by rotating the left testis 720 degrees and fixing with a nylon suture for 4 h. Reperfusion occurred 4 h later by removing the suture, and PRP was administered at a dose of 10 ml (2000 x 10(9)/l) into the left testis via the intra-parenchymal route. Animals were sacrificed at the fourth week, and testes were taken for malondialdehyde (MDA), glutathione (GSH), superoxide dismutase (SOD), myeloperoxidase (MPO), transforming growth factor beta (TGF-beta), and caspase-3 measurements. Results Ischemia/reperfusion caused a significant increase in MDA, MPO and caspase-3 activity, and significant decrease in GSH levels and SOD activity. The PRP treatment helped correct the alterations in SOD, caspase-3, and MPO activities and MDA levels. However, the mean MDA level and MPO activity were not totally restored compared with the controls. Serum testosterone levels of the I/R group were significantly lower compared with the control and I/R + PRP groups. TGF-b and caspase-3 protein expressions were significantly higher in the I/R group compared with the control group and were low with PRP administration compared with I/R groups (summary Table). Discussion The findings of the present study suggest that PRP, by inhibiting neutrophil infiltration and oxidative stress and increasing antioxidant defense, exerts protective effects on testicular tissues against I/R. This study had some limitations: a scoring system was not used in the assessment of spermatogenesis in the histopathological findings and specific testis cell types were not histologically assessed. Conclusions In light of the biochemical, histological and, especially, hormonal findings, intraparenchymal PRP injection may have a protective effect in testicular tissue against I/R injury.
Keywords: Testicular torsion; Inflammation; Ischemia/reperfusion; Platelet-rich-plasma; Testosterone; EXPERIMENTAL TESTICULAR TORSION; ISCHEMIA-REPERFUSION INJURY; CONTRALATERAL TESTIS; MODEL; MECHANISMS; DETORSION; DURATION; PROTEIN